Towards abolition of immunogenic structures in insect cells: characterization of a honey-bee (Apis mellifera) multi-gene family reveals both an allergy-related core α1,3-fucosyltransferase and the first insect Lewis-histo-blood-group-related antigen-synthesizing enzyme - Rendić, Dubravko (Portland Press Ltd., 2007)
Glycoproteins from honey-bee (Apis mellifera), such as phospholipase A(2) and hyaluronidase, are well-known major bee-venom allergens. They carry N-linked oligosaccharide structures with two types of α1,3-fucosylation: the modification by α1,3-fucose of the innermost core GlcNAc, which constitutes an epitope recognized by IgE from some bee-venom-allergic patients, and an antennal Lewis-like GalNAcβ1,4(Fucα1,3)GlcNAc moiety. We now report the cloning and expression of two cDNAs encoding the relevant active α1,3-FucTs (α1,3-fucosyltransferases). The first sequence, closest to that of fruitfly (Drosophila melanogaster) FucTA, was found to be a core α1,3-FucT (EC 2.4.1.214), as judged by several enzyme and biochemical assays. The second cDNA encoded an enzyme, most related to Drosophila FucTC, that was shown to be capable of generating the Le(x) [Galβ1-4(Fucα1-3)GlcNAc] epitope in vitro and is the first Lewis-type α1,3-FucT (EC 2.4.1.152) to be described in insects. The transcription levels of these two genes in various tissues were examined: FucTA was found to be predominantly expressed in the brain tissue and venom glands, whereas FucTC transcripts were detected at highest levels in venom and hypopharyngeal glands. Very low expression of a third homologue of unknown function, FucTB, was also observed in various tissues. The characterization of these honey-bee gene products not only accounts for the observed α1,3-fucosylation of bee-venom glycoproteins, but is expected to aid the identification and subsequent down-regulation of the FucTs in insect cell lines of biotechnological importance.